Produção e sensibilidade de isolados brasileiros de Xanthomonas axonopodis pv. citri à bacteriocinas - Bonini, Marcel [UNESP]; Rodrigues Neto, Júlio; Maringoni, Antonio Carlos [UNESP] (Grupo Paulista de Fitopatologia, 2012)
Este trabalho teve por objetivo avaliar a produção e a sensibilidade de 48 isolados brasileiros de X. axonopodis pv. citri (Xac) à bacteriocinas. Pelos resultados obtidos, nenhum isolado de Xac foi sensível às bacteriocinas produzidas pelos isolados bacterianos avaliados.

The aim of this study was to evaluate the production and sensitivity of 48 Brazilian isolates of X. axonopodis pv. citri (Xac) to bacteriocins. Based on the obtained results, no isolate of Xac was sensitive to the bacteriocins produced by the evaluated bacterial isolates.
Production and sensitivity of Brazilian isolates of Xanthomonas axonopodis pv. citri to bacteriocins
Keywords: cancro cítrico; Citrus spp; bactéria; citrus canker; Citrus spp; bacterium